The viroid and viroid-like RNA database. - Lafontaine, D A (1998)
The viroid and viroid-like RNA database is a compilation of all natural sequences published in journals or available from the GenBank and EMBL nucleotide sequence libraries. Several information regarding these RNA species such as the position of their self-catalytic domains and the open reading frame of the human hepatitits delta virus are provided. The database also includes a determination of the likely ancestral sequence of most species and a prediction of the most stable secondary structures of these sequences. This online database is available on the World Wide Web (http://www.callisto.si.usherb.ca/[symbol: see text]jpperra ). It should provide an excellent reference point for further phylogenetic and structure-function studies of these RNA species.